A STUDY OF ACHIEVEMENT MOTIVATION AND ADJUSTMENT AMONG ADOLESCENT STUDENTS - Dadhich, Anita; Gautam, Nisha Kumari (International Journal of Research -GRANTHAALAYAH, 2025)
This study analyzes the relationship between achievement motivation and adjustment among adolescent students. The objective of the study was to determine the correlation between these two variables and to examine the differences based on various background factors (gender, class, school type). A sample of 200 students was selected. Standardized achievement motivation questionnaires and adjustment inventories were used for data collection. The collected data were analyzed using descriptive statistics, correlation, and t-tests. The results revealed a positive and significant correlation between achievement motivation and adjustment.